The Influence of Work Motivation, Work Discipline and Job Satisfaction on the Performance of Bima Regency Population and Civil Registration Service Employees - Dina Fitriani; Sulaimiah Sulaimiah; Santi Nururly (Lafadz Jaya Publisher, 2023)
This research aims to determine the influence of work motivation, work discipline and job satisfaction on the performance of Bima Regency Population and Civil Registration Service employees. This research consists of independent variables, namely work motivation, work discipline and job satisfaction, as well as the dependent variable, namely performance. The type of research used is Associative-Causal Research. The population in this study were all employees of the Bima Regency Population and Civil Registration Service, totaling 54 employees. The results show that work motivation has a positive and significant effect on the performance of Bima Regency Population and Civil Registration Service employees. Work discipline has a positive and significant effect on the performance of Bima Regency Population and Civil Registration Service employees.